El problema de la congestión del transporte urbano en Lima y Callao, los agentes comprometidos y el sistema perverso de incentivos: hipótesis para las alternativas de solución - Pereyra Nolasco, Felipe Guillermo (2021)
The present investigation, of an exploratory nature, is oriented to the study of urban transport congestion in the metropolis of Lima and Callao. Congestion is usually defined as the excess demand for roads resulting from an oversupply of vehicles, particularly public transport vehicles. In this research, an alternative solution is proposed in reverse: the repression of private transport and the promotion of public transport.